IMPLEMENTASI KEBIJAKAN BADAN USAHA MILIK DESA UNTUK PENDAPATAN DESA DI KABUPATEN TRENGGALEK - Kuncahyo, Edy (DIA: Jurnal Administrasi Publik, 2018)
The establishment of Village-Owned Enterprises (Badan Usaha Milik Desa/BUMDes) in Trenggalek Regency was carried out simultaneously in the 2001 Budget Year throughout the village with 152 pieces still not in accordance with Law Number 22 of 1999 concerning Regional Government. This Village Decree was made by the Village Head and Village Deliberation Institution (Lembaga Masyarakat Desa/LMD) and for its approval by the Regent’s decision. It was supposed that after the Village Representative Body was formed in 2002, then the legal product of the establishment of a Village Owned Business Entity in the form of a Village Decree was changed to a Village Regulation. Facts in the field of Village-Owned Enterprises in Trenggalek Regency have only changed the legal product of its establishment in 2011 and 2012 after 39th Minister of Home Affairs Regulation concerning Village-Owned Enterprises and Regional Regulations of Trenggalek Regency that regulate Village-Owned Enterprises in 2010. the implementation of the policy on the development of village income sources through Village-Owned Enterprises in Trenggalek Regency? This research approach uses qualitative. Using the Goerge C. Edward III Theory, there are 4 variables that influence the implementation of the policy, namely (1) communication, (2) resources, (3) disposition, and (4) bureaucratic structure, it is felt that there are 1 (one) variables namely the public support variable. The result is that the implementation of the Village income source development policy through Village Owned Enterprises in Trenggalek Regency can be declared successful, with categories namely 67 BUMDesa good, 24 BUMDes moderate and 61 BUMDes less and until the study was carried out no BUMDes was dissolved.